Phytochemical investigation of Millettia dorwardi Coll. et Hemsl. (June 2015) - Chen, Kai; Tang, Huan; Wu, Bo; Li, Shucai; Peng, Aihua; Ye, Haoyu; Chen, Lijuan
Abstract: The first phytochemical investigation on the vine stems of Millettia dorwardi Coll. et Hemsl led to the isolation of ten flavonoids (isoafrormosin1, formononetin2, afrormosin3, padmakastein4, liquiritigenin5, 4 H -1-Benzopyran-4-one, 7-hydroxy-5, 8-dimethoxy-3-(4-methoxyphenyl)-isoflavone6, 4 H -1-Benzopyran-4-one, 7-hydroxy-3-(3-hydroxy-5-methoxyphenyl)-6-methoxy8, 4 H -1-Benzopyran-4-one, 6-methoxy-3-(4-methoxyphenyl)-6, 4′-dimethoxyisoflavone9, irisolidone10, prunetin11 ), one heterocycle (5-5′-dibuthoxy-2-2′-bifuran7 ) and one new isoflavone glycoside (4 H -1-Benzopyran-4-one, 5-hydroxymethyl-3-(4-methoxyphenyl)-6-β-d -glucopyranoside-isoflavone12 ). Their structures were determined by extensive analysis of their spectroscopic data. Among them, compounds4, 6 –10, 12 were for the first time isolated from this genus. The chemotaxonomic importance of these compounds was also summarized. Highlights: This is the first phytochemical investigation of Millettia dorwardi Coll. et Hemsl. Six compounds are for the first time isolated from the genus Millettia and one new isoflavone glycoside is isolated. These isoflavones in Millettia dorwardi Coll. et Hemsl have some significance for the identification of the genus Millettia .